Semantic web based integration of knowledge resources for supporting collaboration - Podgorelec, Vili (Informatica (Ljubljana), 2007)
In the paper we present the importance of collaboration between researchers for the improvement of their creativity. A unified methodology to support collaboration strategies of researchers and research teams based on knowledge sharing is introduced. We argue that a defined methodology together with an efficient technological system supporting the methodology should improve the creativity of research teams and consequentially facilitate the development. Based on the required functionalities of such a system, we propose the semantic web as the underlying technology. It is indicated how the semantic web technologies could pro vide the necessary solutions for the integration ofdata resources, the transformation of data into valuable knowledge, the effective use of knowledge by intelligent information services and knowledge sharing both within an organization and inter-organizationally. Finally, the prototype architecture of an intelligent agent within a database system is outlined, which serves as an information integration mechanism.
Keywords: informatika; information science; upravljanje z znanjem; semantični splet; sodelovanje